(untitled) - Luter, Boyd; McReynolds, Kathy, 1960- (Grand Rapids, MI Baker, 1997)
Includes bibliographical references.
Keywords: Women in the Bible; Bible. N.T. -- biography; Christian life -- Biblical teaching